Comprehensive analysis of cuproptosis in immune response and prognosis of osteosarcoma - Li, Mingzhe; Song, Qiang; Bai, Yunfeng; Hua, Feng; Wu, Tao; Liu, Jun (Frontiers in Pharmacology, 2022)
Copper-induced cell death, a form of apoptosis, has been extensively investigated in human diseases. Recent studies on the mechanisms underlying copper-induced cell death have provided innovative insights into copper-related toxicity in cells, and this form of programmed cell death was termed cuproptosis. Herein, we conducted a comprehensive analysis to determine the specific role of cuproptosis in osteosarcoma. Using consensus clustering analysis, patients with osteosarcoma from the TARGET database were classified into subgroups with distinct cuproptosis-based molecular patterns. Accordingly, these patients displayed diverse clinicopathological features, survival outcomes, tumor microenvironment (TME) characteristics, immune-related scores, and therapeutic responses. Furthermore, we constructed a cuproptosis-based risk signature and nomogram, as well as developed a cuproptosis score for improved patient characterization. The prognostic model and cuproptosis score were well validated and confirmed to efficiently distinguish high- and low-risk patients, thereby affording great predictive value. Finally, we verified the abnormal expression of prognostic CUG in OS patients by immunohistochemistry. In conclusion, we suggest that cuproptosis may play an important role in regulating the TME features, tumor progression and the long-term prognosis of osteosarcoma.